ANALISIS SURFACE ROUGHNESS DAN MATERIAL REMOVAL RATE PADA PROSES SINKER-EDM MENGGUNAKAN ELEKTRODA GRAPHITE - Muhamad Ardiansyah; Amri Abdulah; Sukarman (Jurnal Teknologika, 2022)
Electrical discharge machining (EDM) is a non-conventional machining process by feeding the workpiece material by means of an electric spark (spark) through the gap between the electrode and the workpiece containing a dielectric fluid. The EDM process is influenced by the material being processed, electrode material, discharge current, spark on time, spark gap, dielectric fluid and so on. The combination of these parameters will produce different machining characteristics. The purpose of this study was to determine the value of the material removal rate and surface roughness of the workpiece (Surface Roughnes), using graphite electrodes and using the Taguchi method to determine the optimal parameters by varying the current parameters 10A, 13A. , 16A, spark on time 210µ, 340µ, 400µ and gap 40, 45, 50.